Postcards from an Urban Processor - Petra Kempf (Oz, 2005)
The city can be found nowhere, anywhere and everywhere. Across the world, cities are prospering as systems of interwoven networks, ranging from infrastructural connections to never-ending lines of gossip—backed up by the technological progress and the increased mobility of a transient society.